The Phenomenon of Lifelong Learningindividuals with Visual Impairments in the Context of Inclusion - Trefilikova, Tereza (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
The aim of this paper titled "The Phenomenon of lifelong learning individuals with visual impairments in the context of inclusion "is to acquaint the reader with the basic information that relate to aspects of inclusion and lifelong education of individuals with visual impairments, to provide an overview of basic documents and European standards that relate to the topic and present the main aspects that fundamentally influence the process of education for persons with visual disabilities. "This paper is dedicated to project the impact of subjective perception of disability / presence of chronic illness and the concept of health awareness and literacy (IGA_PdF_2015_003)".